2014
DOI: 10.1155/2014/492703
|View full text |Cite
|
Sign up to set email alerts
|

Crude Ethanol Extract of Pithecellobium ellipticum as a Potential Lipid‐Lowering Treatment for Hypercholesterolaemia

Abstract: If left untreated, hypercholesterolaemia can lead to atherosclerosis, given time. Plants from the Fabaceae family have shown the ability to significantly suppress atherosclerosis progression. We selected four extracts from Pithecellobium ellipticum, from the Fabaceae family, to be screened in a 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) assay. The ethanol extract, at a concentration of 500 μg/mL, exhibited superior inhibition properties over the other extracts by demonstrating 80.9% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Atorvastatin has been known to exercise its lipid-lowering effect by competitive inhibition of HMG-CoA reductase, which is the key enzyme for cholesterol biosynthesis. Studies have revealed that terpenoids, steroids, flavonoids, and phenolic compounds are responsible to prevent binding of HMG-CoA to HMG-CoA reductase, either by working individually or synergistically within the plant extract [21]. Our results of wheat bran extract showing similar effect as that of statin in hyperlipidemic rabbits are in agreement with the study by Reddy [22].…”
Section: Discussionsupporting
confidence: 92%
“…Atorvastatin has been known to exercise its lipid-lowering effect by competitive inhibition of HMG-CoA reductase, which is the key enzyme for cholesterol biosynthesis. Studies have revealed that terpenoids, steroids, flavonoids, and phenolic compounds are responsible to prevent binding of HMG-CoA to HMG-CoA reductase, either by working individually or synergistically within the plant extract [21]. Our results of wheat bran extract showing similar effect as that of statin in hyperlipidemic rabbits are in agreement with the study by Reddy [22].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our recent studies demonstrated a positive effect of fermented Lady Joy bean flour on modulating antioxidant and detoxifying enzymes through the Nrf‐2 pathway, inhibiting NF‐kB activation and reducing endoplasmic reticulum stress in primary cultures of rat hepatocytes as in human microvascular endothelial cells and endothelial progenitor cells under various oxidative insults (Gabriele et al., ; Lucchesi et al., ; La Marca et al., ). Additionally, similar to the crude extract of plants belonging to the Fabaceae family and mung bean powder containing cholesterol‐lowering agents (Wong et al., ), also our fermented Lady Joy flour could be able to counteract atherosclerosis progression. Further analysis will be focused on the assessment of lipid‐lowering compounds in fermented Lady Joy flour.…”
Section: Discussionmentioning
confidence: 65%
“…. plants belonging to the Fabaceae family and mung bean powder containing cholesterol-lowering agents (Wong et al, 2014), also our fermented Lady Joy flour could be able to counteract atherosclerosis progression. Further analysis will be focused on the assessment of lipid-lowering compounds in fermented Lady Joy flour.…”
Section: Health Nutrition and Foodmentioning
confidence: 91%